"Being the main character but not always involved in one's own care transition" - a qualitative descriptive study of older adults' experiences of being discharged from in-patient care to home - Emelie Ingvarsson; Kristina Schildmeijer; Heidi Hagerman; Catharina Lindberg (BMC, 2024)
Abstract Background The growing number of older adults with chronic diseases challenges already strained healthcare systems. Fragmented systems make transitions between healthcare settings demanding, posing risks during transitions from in-patient care to home. Despite efforts to make healthcare person-centered during care transitions, previous research indicates that these ambitions are not yet achieved. Therefore, there is a need to examine whether recent initiatives have positively influenced older adults' experiences of transitions from in-patient care to home. This study aimed to describe older adults' experiences of being discharged from in-patient care to home. Methods This study had a qualitative descriptive design. Individual interviews were conducted in January-June 2022 with 17 older Swedish adults with chronic diseases and needing coordinated care transitions from in-patient care to home. Data were analyzed using inductive qualitative content analysis. Results The findings indicate that despite being the supposed main character, the older adult is not always involved in the planning and decision-making of their own care transition, often having poor insight and involvement in, and impact on, these aspects. This leads to an experience of mismatch between actual needs and the expectations of planned support after discharge. Conclusions The study reveals a notable disparity between the assumed central role of older adults in care transitions and their insight and involvement in planning and decision-making.